Sorcha: A Solar System Survey Simulator for the Legacy Survey of Space and Time - Merritt, Stephanie R.; Fedorets, Grigori; Schwamb, Megan E.; Cornwall, Samuel; Bernardinelli, Pedro H.; Juric, Mario; Holman, Matthew J.; Kurlander, Jacob A.; Eggl, Siegfried; Oldag, Drew; West, Maxine; Kubica, Jeremy; et al. (American Astronomical Society, 2026)
The upcoming Legacy Survey of Space and Time(LSST)at the Vera C. Rubin Observatory is expected torevolutionize solar system astronomy. Unprecedented in scale, this 10 yr wide-field survey will collect billions ofobservations and discover a predicted similar to 5 million new solar system objects. Like all astronomical surveys, itsresults will be affected by a complex system of intertwined detection biases. Survey simulators have long beenused to forward-model the effects of these biases on a given population, allowing for a direct comparison to realdiscoveries. However, the scale and tremendous scope of the LSST requires the development of new tools. In thispaper we presentSorcha, an open-source survey simulator written inPython. Designed with the scale ofLSST in mind,Sorchais a comprehensive survey simulator to cover all solar system small-body populations. Itsflexible, modular design allowsSorchato be easily adapted to other surveys by the user. The simulator is builtto run both locally and on high-performance computing clusters, allowing for repeated simulation of millions tobillions of objects(both real and synthetic).